2021
DOI: 10.1002/eat.23533
|View full text |Cite
|
Sign up to set email alerts
|

A two‐week daily diary study examining the association between daily self‐compassion and symptoms of bulimia nervosa

Abstract: Objectives: Individuals with symptoms of bulimia nervosa (BN) are more likely to binge and purge on days of greater negative affect. Given that self-compassion helps individuals cope more adaptively with distress, the present study examined the contribution of daily fluctuations in self-compassion to eating disorder symptoms in women who endorse symptoms of BN. The directionality of these associations was also examined.Method: For 2 weeks, 124 women who met the DSM-5 criteria for BN completed nightly measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…First, with its frequent assessments, the EMA methodology is well-suited to capture the within-person changes (Shiffman et al, 2008 ), which SC evidently displays. In this study, we found an intra-class correlation (ICC) of 0.64, which is similar to the ICCs reported by the small number of other studies assessing SC daily or several times daily (e.g., Breines et al, 2014 ; Katan & Kelly, 2021 ). This ICC indicates that a substantial amount of SC variance was attributable to within-person variance, suggesting that SC is, indeed, not only a stable personality trait but also a fluctuating state.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, with its frequent assessments, the EMA methodology is well-suited to capture the within-person changes (Shiffman et al, 2008 ), which SC evidently displays. In this study, we found an intra-class correlation (ICC) of 0.64, which is similar to the ICCs reported by the small number of other studies assessing SC daily or several times daily (e.g., Breines et al, 2014 ; Katan & Kelly, 2021 ). This ICC indicates that a substantial amount of SC variance was attributable to within-person variance, suggesting that SC is, indeed, not only a stable personality trait but also a fluctuating state.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, a few non-interventional ambulatory studies have conceptualized SC as a state varying across time using daily diary or ecological momentary assessment (EMA) methods, finding important implications for well-being. For instance, daily diary studies found that, on days when individuals reported higher appearance-related or global SC than usual, they indicated healthier eating behaviors (e.g., Breines et al, 2014 ; Kelly & Stephen, 2016 ), a better body image (Kelly & Stephen, 2016 ), less perceived stress (Li et al, 2020 ), and, overall, a lower probability for clinical impairment due to pathological eating habits compared to other days (Katan & Kelly, 2021 ). To our knowledge, only two EMA studies in the field of SC exist so far assessed SC several times throughout the day, finding similar benefits of momentary SC.…”
mentioning
confidence: 99%
“…Given self-compassion is a functional way of responding to life adversity and daily challenges, ESM offers unprecedented insight into the nature and function of self-compassion within the context of daily life. ESM has been applied to self-compassion in daily life in both clinical (Katan & Kelly, 2021) and community samples (Jazaieri et al, 2016;Thøgersen-Ntoumani et al, 2017). Katan and Kelly (2021) used a daily diary method to monitor self-compassion and eating pathology in women diagnosed with bulimia nervosa over two weeks.…”
Section: Experience Sampling Methods (Esm) In Self-compassion Researchmentioning
confidence: 99%
“…ESM has been applied to self-compassion in daily life in both clinical (Katan & Kelly, 2021) and community samples (Jazaieri et al, 2016;Thøgersen-Ntoumani et al, 2017). Katan and Kelly (2021) used a daily diary method to monitor self-compassion and eating pathology in women diagnosed with bulimia nervosa over two weeks. Between-persons analyses found higher daily self-compassion was associated with less dietary restraint and clinical impairment but was unrelated to binge eating and compensatory behaviours.…”
Section: Experience Sampling Methods (Esm) In Self-compassion Researchmentioning
confidence: 99%
“…Research suggests that self-compassion levels vary between people, with certain individuals reporting higher trait levels than others [ 17 ], and also within a person, with a given individual responding to their distress more self-compassionately on some days compared to other days [ 18 , 19 ]. In individuals with eating disorders, both daily [ 20 , 21 ] and trait [ 22 , 23 ] self-compassion levels have been consistently linked to reduced eating pathology, and self-compassion interventions have been found to reduce eating disorder symptoms over time [ 23 25 ]. Research has yet to explore whether self-compassion might also promote mental health, and specifically adaptive coping, in this population.…”
Section: Introductionmentioning
confidence: 99%